Effectiveness of Glycerin Magnesium Sulphate Versus Heparin Benzyl Nicotinate Application Among Children with Phlebitis - Dahal, Akriti Shree; Tuitui, Roshani; Shrestha, Purna Devi; Sharma, Bharati; Acharya, Sharada; Dahal, Priyanka (Journal of Nepal Paediatric Society, 2020)
Introduction: Phlebitis is the most common complication of intravenous infusion therapy. Incidence of phlebitis in children receiving intravenous therapy has been reported to be as high as 71.25%. The study was done to find out the effectiveness of glycerin magnesium sulphate versus heparin benzyl nicotinate application in children with phlebitis. Methods: A pre-post control group design was used. A total of 43 subjects were randomly assigned into two groups [22 in experimental (glycerin magnesium sulphate application) and 21 in control (heparin benzyl nicotinate application) group] by lottery method. Data was collected using Modified Visual Infusion Phlebitis (VIP) Score. Results: The comparison between VIP score was based on observations made before the interventions and at 12, 24, 36 and 48 hours after the intervention. Independent t tests showed significant difference in reduction of VIP score in experimental and control group after 12 hours and 24 hours of intervention. The study demonstrated that there is no statistically significant difference in reduction of VIP score among the subjects in experimental and control group at 12 hours (p = 0.219), 24 hours (p = 0.349), 36 hours (p = 0.695) and 48 hours (p = 0.424) after the intervention. Conclusion: The study concludes that both glycerin magnesium sulphate and heparin benzyl nicotinate can be used effectively among children with phlebitis. However, after 24 hours of phlebitis, an alternative intervention needs to be used.